The distribution across the three NPS categories. - Vanessa Gabriela Yarza Navarro-Schär (22566769) (2025)
Detractors, passives, and promoters were assessed for both the group of low trust customers and high trust customers. The floating values depicted above each bar symbolize the proportional representation of each category within its respective group.